PENINGKATAN HASIL KELILING DAN LUAS BANGUN DATAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 04 CUBADAK AIR KOTA PARIAMAN - Yulia Syafitri, Febrina; Ahmad, Syafri; Hendri, Sherlyane; Zainil, Melva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of students in Mathematics learning, especially the material of perimeter and area of ​​flat shapes, in grade V of SDN 04 Cubadak Air, Pariaman City. This problem is characterized by low student involvement in the learning process and many students who have not achieved the Learning Objectives Achievement Criteria (KKTP). This study aims to describe the improvement of student learning outcomes through the application of the Problem Based Learning (PBL) model. This research is a Classroom Action Research (CAR) with a qualitative and quantitative approach implemented in two cycles. Cycle I consists of two meetings, while cycle II consists of one meeting. Each cycle includes the planning, implementation, observation, and reflection stages. Data were collected through test and non-test techniques. The research subjects were teachers and 22 grade V students of SDN 04 Cubadak Air, Pariaman City. The results showed an increase in all observed aspects. The assessment of the teaching module increased from an average of 86.05% in cycle I to 97.2% in cycle II. The implementation of learning, in terms of teachers 89.1% and students 87.49, increased to 96.4%. Student learning outcomes also increased from an average of 72.65 in cycle I to 85.49 in cycle II. Thus, it can be concluded that the implementation of the Problem Based Learning model is effective in improving student learning outcomes on the material of the perimeter and area of ​​flat shapes in class V SDN 04 Cubadak Air Kota Pariaman.